Implementing the Game-Based Learning Model Through the Marbel Nusantara Culture Application to Enhance Learning Motivation in Elementary School Students - Ajeng Sri Rahmadani; Dianasari Dianasari; Hanikah Hanikah (Journal of Educational Sciences, 2026)
This study aimed to improve students’ learning motivation through the implementation of the Game-Based Learning model supported by the Marbel Nusantara Culture application in Pancasila Education on the topic of Unity in Diversity. The study employed the Kemmis and McTaggart Classroom Action Research model, conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 22 fifth-grade students of SD Negeri 3 Kenanga. Data were collected through teacher and student activity observations and a learning motivation questionnaire. The questionnaire data were analyzed using quantitative descriptive analysis, while the observation and reflection data were analyzed using qualitative descriptive analysis. The findings showed that students’ learning motivation increased from 65.91% in the pre-cycle to 88.95% in cycle I and remained in the very high category at 89.36% in cycle II. The observation results also indicated that students became more active, confident, collaborative, and focused during the learning process, while the teacher managed the learning activities more effectively. These findings indicate that the implementation of Game-Based Learning supported by the Marbel Nusantara Culture application can support improvements in students’ learning motivation and create a more active, interactive, and enjoyable learning process in Pancasila Education.